MORPHOLOGICAL ALTERATIONS OF RED BLOOD CELLS CAUSED BY OVERDOSES OF SILDENAFIL - FAISAL M ALZAHARNI; FATHELRAHMAN M HASSAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to investigate whether the overdose of sildenafil (Viagra) causes red blood cytotoxicity in rats by seeing the morphological alterations. Methods: Fifteen rats which were randomly divided into four groups of rats were received intraperitoneal injections of sildenafil. The sildenafil was dissolved in sterile saline 45% for three groups except the control group. They were injected for 5 days in three doses as followed (0.3 mg/rat for G1, 0.5 mg/rat for G2, and 1 mg/rat for G3). Blood smears were made to test the alterations in the blood cells after injection. Results: The result indicated the presence of a relationship between sildenafil overdosing and red blood cell morphology. Mild-to-moderate alterations of hematological morphology were observed. The hematologic morphology variation was observed in size, shape, and distribution of hemoglobin using light microscope and confirmed by the scanned electronic microscope. Conclusion: Possible hemotoxicity effects of sildenafil overdosing might be existing, which might be proportional to the duration of usage. However, further studies are recommended properly illustrate the effect of usage duration on sildenafil overdosing toxicity on red blood cells.